Efficacy of a Transdiagnostic Self-Help Internet Intervention for Reducing Depression, Anxiety, and Suicidal Ideation in Adults: Randomized Controlled Trial - Batterham, Philip J; Calear, Alison L; Farrer, Louise; Gulliver, Amelia; Kurz, Ella (JMIR Publications, 2021)
BackgroundLow-intensity self-guided mental health interventions that are delivered on the web may meet the needs and preferences of adults with mild to moderate symptoms. However, few clinical trials have examined the effectiveness of self-guided transdiagnostic interventions within a naturalistic setting. ObjectiveThis randomized controlled trial (RCT) tests the effectiveness of the video-based transdiagnostic intervention FitMindKit in reducing depression symptoms (primary outcome), anxiety symptoms, disability, and suicidal ideation, relative to an attention-matched control condition called HealthWatch. MethodsThe RCT was conducted with adults living in the Australian Capital Territory, Australia. Participants (n=1986) were recruited through the web using social media advertisements, screened for psychological distress, and then randomized to receive one of two 4-week programs: FitMindKit (12-module psychotherapy intervention) or HealthWatch (12-module program providing general health information). Participants were assessed at baseline and at 4 weeks postbaseline. To maintain the ecological validity of the trial, participants completed brief assessments and interventions without direct researcher contact or incentives. ResultsMixed model repeated-measures analyses of variance demonstrated that FitMindKit significantly improved depression symptoms (F1,701.7=3.97; P=.047), along with panic symptoms (F1,706.5=5.59; P=.02) and social anxiety symptoms (F1,680.0=12.37; P<.001), relative to the attention control condition. There were no significant effects on other outcomes. ConclusionsSelf-guided transdiagnostic interventions can be beneficial when delivered directly to end users through the internet. Despite low adherence and small effect sizes, the availability of such interventions is likely to fill a critical gap in the accessibility of mental health services for the community. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12618001688279; http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=376113. International Registered Report Identifier (IRRID)RR2-10.1016/j.conctc.2019.100341